Cognitive dysfunction as a major determinant of disability in patients with heart failure: results from a multicentre survey - Giuseppe Zuccalà (2001)
This exploratory, randomised, double-blind, double-dummy, multicentre, cross-over study explored the effect of 6 weeks of treatment with tiotropium/olodaterol (T/O) versus fluticasone propionate/salmeterol (F/S) on left ventricular filling in patients with chronic obstructive pulmonary disease with functional residual capacity (FRC) >120% predicted and postbronchodilator improvement of FRC ≥7.5%. Overall, 76 patients were randomised across nine sites. Treatment with T/O or F/S increased left ventricular end-diastolic volume index from baseline (adjusted mean change: T/O: 2.317 mL/m2, F/S: 2.855 mL/m2), with no statistically significant difference between treatments. However, T/O resulted in a significantly greater reduction in lung hyperinflation versus F/S (FRC plethysmography absolute change from baseline: F/S: –0.329 L, T/O: –0.581 L).